EFEKTIVITAS METODE PEMBELAJARAN FISIOTERAPI TERHADAP KETRAMPILAN BERFIKIR KRITIS MAHASISWA UNIVERSITAS WIDYA DHARMA KLATEN - Zuyina Luklukaningsih (Universitas Muhammadiyah Klaten, 2019)
The purpose of this study was to determine 1) the effectiveness of the physiotherapy learning method on the critical thinking skills of Widya Dharma Klaten University students, 2) the critical thinking skills of Widya Dharma University students of Physiotherapy, Klaten. The subjects of this study were students of the Widya Dharma Klaten University Physiotherapy study program, with the criteria of students who were active in lectures and had high learning motivation. These students were either male or female who experienced several learning problems, for example lack of focus in attending lectures, difficulty memorizing Latin for certain subjects, for example anatomy. The results of the descriptive analysis of the lowest empiric data for the pre-test were 140 and the highest score was 149, with an average value of 143 and a standard deviation of 3,450. While the results of the descriptive analysis of the lowest empiric data for the posttest were 143 and the highest score was 175, with an average value of 159 and a standard deviation of 11.05. These data indicate an increase in the average value of critical thinking skills among Widya Darma Klaten University students Based on the results of the study, it can be concluded that there is a difference in statistical values ​​between the pre-test group (before the learning method is used) and the Post-test group (after being given the learning method). So it can be said that the physiotherapy learning method is effective on students' critical thinking skills